2019
DOI: 10.1016/j.jid.2018.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Pyrophosphate Modulates Calcification in a Mouse Model of Pseudoxanthoma Elasticum: Implication for Treatment of Patients

Abstract: Pseudoxanthoma elasticum is a heritable disease caused by ABCC6 deficiency. Patients develop ectopic calcification in skin, eyes, and vascular tissues. ABCC6, primarily found in liver and kidneys, mediates the cellular efflux of ATP, which is rapidly converted into inorganic pyrophosphate (PPi), a potent inhibitor of calcification. Pseudoxanthoma elasticum patients and Abcc6 e/e mice display reduced PPi levels in plasma and peripheral tissues. Pseudoxanthoma elasticum is currently incurable, although some pall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 55 publications
(96 reference statements)
2
28
0
Order By: Relevance
“…animal model used to study human diseases, the biology of rodents can be noticeably divergent 53 . Abcc6 −/− mice, despite the known differences with the human phenotype 54 , have been extraordinarily useful for the study of PXE 55,56 and the development of therapeutic approaches 49,[57][58][59][60] . However, mice present singular differences in lipoproteins and atherosclerosis development 61 .…”
Section: Discussionmentioning
confidence: 99%
“…animal model used to study human diseases, the biology of rodents can be noticeably divergent 53 . Abcc6 −/− mice, despite the known differences with the human phenotype 54 , have been extraordinarily useful for the study of PXE 55,56 and the development of therapeutic approaches 49,[57][58][59][60] . However, mice present singular differences in lipoproteins and atherosclerosis development 61 .…”
Section: Discussionmentioning
confidence: 99%
“…PPi might therefore be an important biomarker for the severity or predict the progression of PXE. Intraperitoneal PPi supplementation halted calcification in mice and oral PPi increased plasma PPi levels in healthy volunteers [9,31]. In addition, several other therapies that interfere in the PPi homeostasis or ectopic calcification are being developed for PXE and related disorders [32].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PXE and GACI as well as Abcc6 −/− and Enpp1 mutant (tiptoe walking: ttw/ttw) mice have a reduced plasma PPi level, explaining, at least in part, their mineralization disorder [22]. Of note, PPi treatment is sufficient to prevent ectopic mineralization in both Abcc6 −/− and Enpp1 ttw/ttw murine models [33][34][35].…”
Section: Pathophysiology Of Pxe Gaci and Acdc: Pyrophosphate Deficiencymentioning
confidence: 99%
“…Abcc6 −/− mice expressing a functional human ABCC6 protein in the liver or supplemented with PPi were protected against kidney calcification [33,34]. It has been shown that oral PPi is partly absorbed in human subjects and increases serum PPi circulating levels.…”
Section: The Abcc6 −/− Murine Model: a Tool To Identify Randall's Plamentioning
confidence: 99%